A Comparative Study of Dermatoscopic Features of Acne-related Postinflammatory Hyperpigmentation in Facial and Nonfacial Areas in Asian Patients - Jurairattanaporn N. (2023)
BACKGROUND: Postinflammatory hyperpigmentation (PIH) is a common problem, especially in patients with darker skin tones. It can occur on any area of the body following external injuries or intense inflammatory conditions. However, there is limited evidence regarding the differences in dermatoscopic patterns between facial acne-related PIH and nonfacial acne-related PIH. OBJECTIVE: We sought to determine the dermatoscopic features of acne-related PIH in facial and nonfacial areas in an Asian population. METHODS: Patients with acne-related PIH in both facial and nonfacial areas were enrolled. Baseline demographic data, location, and duration of PIH were recorded. Dermatoscopic and clinical pictures of each patient were taken from the darkest PIH lesions of both areas. Differences in dermatoscopic patterns were analyzed. RESULTS: Fifty patients were enrolled. The mean age was 26.74 (+ 6.75) years, and the Fitzpatrick Skin Types were III (66%) and IV (34%). In terms of morphological patterns of melanin, nonfacial PIH showed a significantly more regular pigment network than facial PIH (100% vs. 20%, p<0.05), while facial PIH exhibited a more pseudoreticular pigment network than nonfacial PIH (70% vs. 0%, p<0.05). In terms of vascularity, facial PIH demonstrated more telangiectasia and an increased vascular component compared to nonfacial PIH (56% vs. 16%, p<0.05). Moreover, hypopigmentation within the PIH lesion was demonstrated in both facial and nonfacial lesions (42% vs. 50%, p=0.541). CONCLUSION: Acne-related PIH in facial and nonfacial areas showed different morphological pigment patterns and degrees of vascularity. Dermatoscopic examination should be performed before treatment initiation.